(untitled) - Bagadia, Kishan (New York, 2006)
This book is intended to be a comprehensive practical reference on computerized maintenance for plant engineering personnel and others concerned with plant operations and maintenance management. It applies to industrial plants, utilities, hospitals, and building maintenance. In fact, it applies to all operations involved with equipment and inventory management. Because of its practical usefulness, this book will serve as an excellent hanout in maintenance management courses, seminars and workshops.
Keywords: Plant maintenance,Industrial equipment,Lập kế hoạch duy trì; Data processing,Maintenance and repair,Data processing,Quy trình xử lý dữ liệu